2022
DOI: 10.21037/atm-22-6060
|View full text |Cite
|
Sign up to set email alerts
|

B and T lymphocyte attenuator as a C-reactive protein and IgA associated auxiliary diagnostic marker for pulmonary tuberculosis: a case-control study

Abstract: Background: Screening and identification of hematologic molecular indicators of pulmonary tuberculosis (PTB) is crucial for its diagnose and therapy. Therefore, our work aims to detect the diagnostic value of blood marker B and T lymphocyte attenuator (BTLA) in PTB, and provide a certain theoretical basis for the auxiliary diagnosis of PTB. Methods: Based on the inclusion criteria, 56 Patients with clinically confirmed pulmonary TB by clinical between January 2020 and December 2021 at our hospital were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“… 18 Another study demonstrated that the expression of CD11c + BTLA was positively related to CRP, which might be correlated with inflammatory changes in PTB patients. 29 The present study mainly focused on studying the association of four SNPs (rs1982809, rs2971205, rs75368388, rs9288953) in BTLA gene with PTB risk, while no significant association was found between these SNPs and the risk of PTB. Contrary to our study, previous studies displayed significant correlation between BTLA gene polymorphisms and cancer, autoimmune diseases.…”
Section: Discussionmentioning
confidence: 94%
“… 18 Another study demonstrated that the expression of CD11c + BTLA was positively related to CRP, which might be correlated with inflammatory changes in PTB patients. 29 The present study mainly focused on studying the association of four SNPs (rs1982809, rs2971205, rs75368388, rs9288953) in BTLA gene with PTB risk, while no significant association was found between these SNPs and the risk of PTB. Contrary to our study, previous studies displayed significant correlation between BTLA gene polymorphisms and cancer, autoimmune diseases.…”
Section: Discussionmentioning
confidence: 94%